Data Integrity and Security [DIS] Based Protocol for Cognitive Radio Ad Hoc Networks - Azeem Mohammed Abdul; Syed Umar (Institute of Advanced Engineering and Science, 2017)
In the CRN (cognitive Radio Networks) the main issues to be addressed are spectrum scarcity and inadequate usage of spectrum. The CRN can analyse the unused spectrum, so that CRN users can easily occupy the unused spectrum without blocking the existing Primary Users. In a CRN, routing is a complex issue because of channel diversity. The existing system mainly focuses on the performance analysis of Ad hoc On-Demand Distance Vector (AODV) and the Weight Cumulative Expected transmission time (WCETT). The performance of these protocols are measured and compared in various ways such as the throughput of single radio station multi-channels, equal number of radio stations and channels, multi-radio stations multi-channels. The limitation with these protocols is, whenever a route fails, there is issue to get connected with the other nodes, the other being data integrity, which maintains the no loss of data [LOD]. In our proposed DIS – CRAHN system we overcome these limitations by adding data security and integrity. Security is provided using the RSA algorithm while Integrity is ensured using the SHA algorithm. With the data security we can maintain the shortest path from source to destination and if any route failure occurs then immediate route establishment can be done and data encryption and decryption also be implemented using the random key generation. Results show an improved performance in delay with reasonable throughput, making the protocol an ideal choice for CRNs.